Effectiveness Of Implementation Of Integrated Curriculum At SMA IT Fadhilah Pekanbaru - Lestary, Bella Desfi; Almasdi Syahza; Gimin (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The curriculum is the main foundation in the education system that directs the teaching and learning process and the development of students. This study aims to determine the effectiveness of the implementation of the integrated curriculum at SMA IT Pekanbaru in achieving effective and efficient learning objectives. The method used is a qualitative descriptive approach. Data were collected using interview and documentation techniques. Data sources were taken from the results of interviews with the principal and curriculum representatives as well as written records, information from school documents. The analysis technique used data reduction, data presentation and drawing conclusions. The main findings of the study prove that the implementation of the integrated curriculum has been implemented effectively with the support of collaboration between parents and teachers and active involvement of students. Collaboration between schools and parents is very important in improving discipline and the application of theory in students' daily lives. This study recommends the need for a more comprehensive evaluation of the curriculum implementation process to identify areas that need to be improved. This study is expected to contribute to the development of the curriculum in other schools and enrich the literature on integrated curriculum-based education.